Common mental disorders and resilience in homeless persons - Anna Cláudia Freire de Araújo Patrício; Richardson Augusto Rosendo da Silva; Rossini Freire de Araújo; Rôseane Ferreira da Silva; Géssica Thais de Sousa Nascimento; Thays Domingos de Brito Rodrigues; Maria Amanda Pereira Leite (Associação Brasileira de Enfermagem, 2019)
ABSTRACT Objective: To identify common mental disorders and resilience in homeless persons. Method: Cross-sectional study with 49 homeless persons, assisted in the Casa da Acolhida Adulta and the Specialized Reference Center in a municipality in the Northeast of Brazil. Data collection performed between February and March 2018, using SRQ20 scales for common mental disorders and another for Resilience. Kruskal Wallis test, Student's T-test and Chi-Square test were used. Results: In the study, 61.2% (30) participants have poor sleep; 69.4% (34) feel nervous, tense or worried; 71.4% (35) feel unhappy; 63.3% are unable to play a useful role in their lives; 71.4% (35) have common mental disorders, and 44.9% (22) presented low resilience. Resilience influences common mental disorders, which, in turn, are influenced by gender and age. Conclusion: Professionals who assist homeless persons need to have a look directed at common mental disorders and resilience.